The Coping Stress Differences among Work from Home and Work from Office Individuals - Arri Handayani; Desi Maulia; Padmi Dhyah Yulianti; Primaningrum Dian (Faculty of Psychology, Universitas Semarang, 2024)
Abstract. Working from home and working permanently in the office (work from office) have their problems. These differences indeed lead to different responses in coping with stress. This research aims to analyze the differences in coping with stress in individuals who experience work-from-home and work-from-office periods, as well as analyze coping strategies during the work-from-home period. This research uses a quantitative method, using a t-test. The sampling technique uses purposive random sampling, with the characteristics of the population being married and having children, working in agencies either from home or the office. Data collection techniques used a stress coping scale and an open questionnaire regarding identifying feelings and problems that arise, expressed via Google Forms. Quantitative analysis is carried out using t-tests and descriptive analysis. Based on the Mann-Whitney test, the Mean Rank or average group ranking was obtained, namely for work from home, it was 95,15, and work from office was 94.54 with a significance value of (0.947) > 0.05. The quantitative research results show no difference in coping with stress between individuals who experience the work-from-home period and during the work-from-office period. Meanwhile, the results of the descriptive analysis show that the most dominant feeling during the work-from-home period is anxiety, anxiety, or worry (40.74%), while the problem most frequently experienced by respondents is difficulty dividing their time between office work and homework (26.45 %). In general, coping strategies overcome feelings of worry by conveying hobbies (23.28%), while coping strategies overcome problems during the work-from-home period by interacting online (26.45%) and doing good time management (17.98%).Keywords: Coping Stress; Work from Home; Work from Office